2022
DOI: 10.7717/peerj.13965
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pro-inflammatory cytokines and fatigue in pregnant women

Abstract: Background Fatigue is one of the most prevalent symptoms among pregnant women. In patients with various diseases, pro-inflammatory cytokines are associated with fatigue; however, such associations are unknown in pregnant women. Objectives The objective of this study was to examine the associations between pro-inflammatory cytokines and prenatal fatigue. Methods A cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In postnatal depression, an anti-inflammatory effect might also be of particular relevance, given that notable changes in serum proinflammatory mediators are observed during pregnancy and the postpartum period [ 82 ]. The concentration of TNF-α was found to be elevated in peripheral blood during the entire gestation period [ 83 , 84 , 85 , 86 ], whereas IL-6 and IL-8 levels were observed to increase from the second to the third trimester [ 86 , 87 ]. Christian et al reported increases in the levels of IL-6, TNF-α, IL-8, and IL-1β at 4–6 weeks postpartum compared to those in the third trimester of pregnancy [ 88 ].…”
Section: Biological Mechanisms That Might Underlie Selenium’s Effects...mentioning
confidence: 99%
“…In postnatal depression, an anti-inflammatory effect might also be of particular relevance, given that notable changes in serum proinflammatory mediators are observed during pregnancy and the postpartum period [ 82 ]. The concentration of TNF-α was found to be elevated in peripheral blood during the entire gestation period [ 83 , 84 , 85 , 86 ], whereas IL-6 and IL-8 levels were observed to increase from the second to the third trimester [ 86 , 87 ]. Christian et al reported increases in the levels of IL-6, TNF-α, IL-8, and IL-1β at 4–6 weeks postpartum compared to those in the third trimester of pregnancy [ 88 ].…”
Section: Biological Mechanisms That Might Underlie Selenium’s Effects...mentioning
confidence: 99%